Nurkse-Furtado Hypothesis and Veblen Hypothesis: An Analysis of Brazilian’s determinants of conspicuous goods imports from 2011 to 2020, using a Vector Autorregressive Model (VAR) - Barbieri Camatta, Rafael; Ottoni Teatini Salles, Alexandre; Zambon Monte, Edson (Brazilian Keynesian Review, 2025)
The theoretical literature on conspicuous consumption reveals that this behavior can generate a series of economic and social problems, especially for low-income individuals and underdeveloped countries (Camatta, 2023, Camatta and Salles, 2024). Despite the various theoretical incursions into this subject over the last two and a half centuries, it can be seen that the topic has not been widely addressed quantitatively in economics. This article aims to contribute to this respect by proposing: 1) to construct a time series to measure the variation in conspicuous consumption in Brazil in the period 2011/2020, especially with regard to the import of luxury goods; and 2) to investigate the determinants of this trade. To analyze these determinants, two hypotheses were tested: (i) luxury imports are mainly determined by changes in national income (Nurkse-Furtado hypothesis); and (ii) imports of this category of goods are very inelastic to their average price (Veblen hypothesis). The VAR model used was unable to reject either hypothesis. It was also possible to observe that luxury imports have a high-income elasticity.